Pengaruh Good Corporate Governance dan Kepemilikan Manajemen terhadap Kinerja Keuangan (Studi pada Industri Automotive di BEI) - Djumahir - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Corporate governance is very important in the process of corporate performance. The internal mechanisms of corporate governance can be done through the placement of an independent Commissioner to actively monitor. Greater role for direct management achieve corporate goals. Corporate results is heavily influenced by the shape of management manages the profits. Revenues obtained by a company are actually the result of accounting manipulation, revenue management is important to reach the size appropriate with a will of its shareholders. The proportion of property values by the management company will reduce conflicts of interest between management and shareholders, by the property management will lead the company to achieve better performance. Research is to study the influence of corporate governance and management of the property on your business results. The results of the analysis found that the corporate governance and ownership management determines the performance of the company.Keywords: corporate governance, performance